Study of Dzarrah: Analysis of Wave Functions Potential Non Central Coulombic Rosen Morse - Cecilia Yanuarief (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
It has been obtained a graph of the wave function of Coulombic's non-central potential Schrodinger equation Rosen Morse which is systematically an embodiment of hydrogen atoms and their isotopes. Schrodinger's equation is solved through variable spatial techniques with each variable resolved using a different method so that the radial and angular part wave functions are visualized by Matlab-based computer programming. Visualization of the radial wave function that is formed describes the probability value of the discovery of electrons which are small parts of an atom, while the visualization of the formed angular wave function shows the movement of electrons in an energy level. The mention of the atom itself is already in the Qur'an, Allah says in surah As-Saba verse 3. According to the interpretation of Quraish Shihab the word dzarrah in Arabic refers to a very small object, the size of an ant's child or fine dust. The phrase mitsqalu dzarrah in this verse means the weight of an atom. This implies the presence of a compound whose specific gravity is lighter than an atom.